Kant's Groundwork of the metaphysics of morals : a critical guide - Timmermann, Jens (Cambridge critical guides., 2009)
This collection of essays, by Kant scholars & moral philosophers, discusses Kant's philosophical development & his rejection of earlier moral theories, the role of happiness & inclination in the Groundwork, Kant's metaphysics & theory of value, & his attempt to justify the categorical imperative as a principle of freedom.